2015
DOI: 10.1002/lary.25147
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid treatment regulates mucosal remodeling in chronic rhinosinusitis with nasal polyps

Abstract: 4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 40 publications
1
26
0
1
Order By: Relevance
“…Jiang et al () found that MMP‐7 levels were elevated in patients with oral squamous cell carcinoma. de Borja Callejas et al () have proposed that MMP‐7 may be involved in the formation and remodeling of nasal polyps based on an observed level of expression of MMP‐7 in nasal polyps. They also determined treatment with corticosteroids could be a viable option in regulation the remodeling of the mucosal layer when dealing with rhinosinusitis associated nasal polyps (de Borja Callejas et al, ).…”
Section: Matrix Metalloproteinase‐7mentioning
confidence: 99%
“…Jiang et al () found that MMP‐7 levels were elevated in patients with oral squamous cell carcinoma. de Borja Callejas et al () have proposed that MMP‐7 may be involved in the formation and remodeling of nasal polyps based on an observed level of expression of MMP‐7 in nasal polyps. They also determined treatment with corticosteroids could be a viable option in regulation the remodeling of the mucosal layer when dealing with rhinosinusitis associated nasal polyps (de Borja Callejas et al, ).…”
Section: Matrix Metalloproteinase‐7mentioning
confidence: 99%
“…Epithelial hyperplasia is also seen in lower airway diseases such as cystic fibrosis and COPD. de Borja Callejas et al . demonstrated that oral corticosteroids led to modulation in epithelial remodeling in nasal polyposis, with decreased epithelial hyperplasia and tissue eosinophilia.…”
Section: The Majority Of Chinese Nps Are Neutrophilicmentioning
confidence: 99%
“…4 Use of oral corticosteroid treatment with combined intranasal corticosteroid treatment has been shown to modulate nasal polyp mucosa remodeling through promotion of epithelial repair, regulation of tissue remodeling markers, increasing collagen content, and reducing tissue eosinophil infiltration. 5 Short courses of oral corticosteroids in CRSwNP are associated with significant reduction in polyp size as well as improved CRS symptom scores, nasal endoscopy, and magnetic resonance imaging findings. 6 However, given the heterogeneity of CRS, the presence of nasal polyps as the sole determining factor for oral steroid may be too simplistic and may not account for patients with overlapping or difficult to classify disease.…”
Section: Introductionmentioning
confidence: 95%
“…Oral steroids are recommended for perioperative use among patients with CRSwNP and allergic fungal sinusitis . Use of oral corticosteroid treatment with combined intranasal corticosteroid treatment has been shown to modulate nasal polyp mucosa remodeling through promotion of epithelial repair, regulation of tissue remodeling markers, increasing collagen content, and reducing tissue eosinophil infiltration . Short courses of oral corticosteroids in CRSwNP are associated with significant reduction in polyp size as well as improved CRS symptom scores, nasal endoscopy, and magnetic resonance imaging findings .…”
Section: Introductionmentioning
confidence: 99%